Analisis pendidikan karakter Al-Islam dan Kemuhammadiyahan dalam membentuk nilai beriman, bertaqwa dan berakhlak mulia siswa kelas iv mi Muhammadiyah 01 sukodadi - Yunita Sufi Anggraini; Rizka Novi Irmaningrum; Humairah HUmairah (Jurnal Tematik, 2026)
Character education based on Islamic values plays a crucial role in shaping a generation that is faithful, pious, and morally upright. MI Muhammadiyah 01 Sukodadi, as an Islamic educational institution, is committed to instilling Al-Islam and Muhammadiyah values in its teaching and learning processes, particularly for fourth-grade students. This study aims to explore how the implementation of Al-Islam and Muhammadiyah character education contributes to the development of students’ faith, piety, and noble character. The research employed qualitative methods, including observation, interviews, questionnaires, and documentation. The findings indicate that MI Muhammadiyah 01 Sukodadi has successfully developed students' character holistically, encompassing aspects of faith, morals, intellect, social interaction, and leadership. Students demonstrated a good understanding of Islamic teachings and actively participated in religious activities, although maintaining consistency in worship remains a challenge. Their social interactions with peers and teachers reflected positive attitudes and a strong sense of empathy. However, issues such as impolite behavior and a lack of interest in leadership roles still need to be addressed. Overall, the school has created a supportive educational environment for character development grounded in Islamic and moral values.